2017
DOI: 10.5027/reinnec.v1.i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Química orgánica en contexto y argumentación científica: una secuencia de enseñanza aprendizaje, desafíos y compromisos

Abstract: Actualmente nuestro país presenta niveles de alfabetización científica por debajo de la media de países pertenecientes a la OCDE, visualizar esta realidad nacional nos motiva a colaborar en el desarrollo de competencias científicas, especialmente en la promoción de argumentación. Esta investigación, tiene por objetivo la implementación de una Secuencia bajo el enfoque CTS, específicamente en la competencia de argumentación científica. El diseño e implementación de la SEA permite utilizar al interior del aula m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…However, the teaching of Chemistry is a very complex activity, since it has been observed that, for high school students, understanding Chemistry implies a greater effort compared to other subjects that make up their curriculum (Ávila et al, 2020;Zouiten 2021). In addition to that, one of the factors that affects the decrease in student interest in Chemistry, if not the main one, is the way of approaching the study of this science; Chemistry courses at all levels are overloaded with theoretical information, oriented towards theory testing and rule following (Galagovsky et al, 2003;Morales and Salgado, 2017;Chang, 2020). This causes a total lack of interest in the subject, generating absence in the classroom, which finally culminates in failing the subject.…”
Section: The Importance Of Studying Chemistrymentioning
confidence: 99%
“…However, the teaching of Chemistry is a very complex activity, since it has been observed that, for high school students, understanding Chemistry implies a greater effort compared to other subjects that make up their curriculum (Ávila et al, 2020;Zouiten 2021). In addition to that, one of the factors that affects the decrease in student interest in Chemistry, if not the main one, is the way of approaching the study of this science; Chemistry courses at all levels are overloaded with theoretical information, oriented towards theory testing and rule following (Galagovsky et al, 2003;Morales and Salgado, 2017;Chang, 2020). This causes a total lack of interest in the subject, generating absence in the classroom, which finally culminates in failing the subject.…”
Section: The Importance Of Studying Chemistrymentioning
confidence: 99%
“…La enseñanza de la Química Orgánica en las instituciones educativas se da partir de 1863, en los Países Bajos se implementó como una de las materias regulares que hasta entonces no se había dado en ninguno de los centros educativos, cabe mencionar que no todos tenían el acceso a esta asignatura sino solamente un grupo de jóvenes que pertenecían a las elites sociales de los Países Bajos (Morales & Salgado, 2017).…”
Section: Introductionunclassified
“…Por otra parte, algunos estudios reportan que podría resultar difícil de comprender para los estudiantes la representación molecular de los compuestos orgánicos (García, Valdez y Gómez, 2008;Villaseñor et al, 2013;Cerón et al, 2013;Farré, Zugbi y Lorenzo, 2014;Morales y Salgado, 2017;Ríos, 2017), los mismos que están relacionados con la falta de esfuerzo de ellos o a formas inadecuadas de enseñanza del docente (Galagovsky y Bekerman, 2009) o a dificultades del procesamiento de información del lenguaje químico (Galagovsky, Bekerman, Di Giacomo y Alí, 2014).…”
Section: Introductionunclassified